Bacterial Infections Affect Male Fertility: A Focus on the Oxidative Stress-Autophagy Axis - Wang, Sutian; Zhang, Kunli; Yao, Yuchang; Li, Jianhao; Deng, Shoulong (Frontiers in Cell and Developmental Biology, 2021)
Numerous factors trigger male infertility, including lifestyle, the environment, health, medical resources and pathogenic microorganism infections. Bacterial infections of the male reproductive system can cause various reproductive diseases. Several male reproductive organs, such as the testicles, have unique immune functions that protect the germ cells from damage. In the reproductive system, immune cells can recognize the pathogen-associated molecular patterns carried by pathogenic microorganisms and activate the host’s innate immune response. Furthermore, bacterial infections can lead to oxidative stress through multiple signaling pathways. Many studies have revealed that oxidative stress serves dual functions: moderate oxidative stress can help clear the invaders and maintain sperm motility, but excessive oxidative stress will induce host damage. Additionally, oxidative stress is always accompanied by autophagy which can also help maintain host homeostasis. Male reproductive system homeostasis disequilibrium can cause inflammation of the genitourinary system, influence spermatogenesis, and even lead to infertility. Here, we focus on the effect of oxidative stress and autophagy on bacterial infection in the male reproductive system, and we also explore the crosslink between oxidative stress and autophagy during this process.